ANALISIS DAMPAK STRUKTUR KEPEMILIKAN PADA KEBIJAKAN HUTANG DALAM MENGONTROL KONFLIK KEAGENAN - Masdupi, Erni (Journal of Indonesian Economy and Business, 2005)
This study examines the impact of ownership structure and some control variables on corporate debt policy (debt ratio) in an agency theory context. Control variables are dividend payment, firm size, asset structure, firm profitability and tax rate. This study is based on the previous study by Mohâd et al., (1998), which found that ownership structure of the firmsâs equity (insider ownership, shareholder dispersion and institutional investor) is important in explaining corporate debt policy in a agency theory context.This study is focused on all firm listed on Jakarta Stock Exchange, except financial and insurance firms from 1992 to 1996. The method of analysis is using pooling. The method of data collection is purposive sampling. There are 100 firms year observation.The result of the study shows that insider ownership and institutional investor to be significant and negative determinant of the corporate debt policy (debt ratio). It also indicates that shareholder dispersion is insignificant determinant of debt ratio.Keywords: Debt Ratio, Ownership Structure, Agency Theory, Insider Ownership, Shareholder Dispersion and Institutional Investor.